Integrating the process of Ni (II) ions removal from aqueous solution and cooling of a photovoltaic module by 1.7 MHz ultrasound waves - Zakie Rostami (Journal of Applied Research in Water and Wastewater, 2020)
In this study, Ni+2 removal from aqueous solution was investigated by concurrent usage of Fe3O4 nanoparticles and a high frequency ultrasound (1.7 MHz). In addition to Ni+2 removal, presence of the high frequency ultrasound led to being cooled photovoltaic (PV) module. Studied variables were pH and adsorbent dose (AD). Results indicated that the Ni+2 removal efficiency increased with an increase in the pH ranging from 2 to 9. Furthermore, the Ni+2 removal efficiency boosted by an increase in the AD. However, no significant enhancement in Ni+2 removal efficiency was observed at the AD above 9 g. Generally, the maximum Ni+2 removal efficiency was about 79 % for contact time of 50 min at pH=9 and AD=9 g in the presence of ultrasound. At the efficient condition (pH=9, AD=9 g and contact time=50 min), using ultrasound showed 16-20 % enhancement in Ni+2 removal efficiency compared to no ultrasound usage. From heat transfer view, it was observed that propagation of 1.7 MHz ultrasound into nanofluid significantly has cooled the photovoltaic (PV) module. Moreover, an increase in concentration of nanofluid (AD) showed a positive effect on reduction of heat from the PV module surface and maximum generated power. Obtained data demonstrated that agitating nanofluid by 1.7 MHz ultrasound decreased temperature of the PV module up to 15.5 % compared to no cooling system.